2017
DOI: 10.1177/1076029616689593
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis in Patients With Cirrhosis Undergoing Elective Transjugular Intrahepatic Portosystemic Shunt: Risk Factors, Warfarin Efficacy, and Clinical Outcomes

Abstract: Portal vein thrombosis (PVT) is a common complication in cirrhosis. The aim of this study was to determine risk factors for PVT, assess the efficacy of anticoagulant therapy, and evaluate the effects of PVT on patients with cirrhosis undergoing elective transjugular intrahepatic portosystemic shunt (TIPSS). A total of 101 patients with cirrhosis undergoing elective TIPSS were prospectively studied. After TIPSS, all patients received preventive therapy for PVT and were followed up at 3, 6, 12, and 24 months. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
5
1
2
Order By: Relevance
“…63 In contrast, Wan et al reported that warfarin could effectively promote recanalization in approximately 50% of patients within 1 year in those with de novo post-TIPS PVT. 64 The incidence of PVT in the warfarin group (15%) was 3-fold lower than that in the control group (43%). 64…”
Section: Role Of Transjugular Intrahepatic Portosystemic Shunt For Portal Vein Thrombosis Treatmentmentioning
confidence: 82%
See 1 more Smart Citation
“…63 In contrast, Wan et al reported that warfarin could effectively promote recanalization in approximately 50% of patients within 1 year in those with de novo post-TIPS PVT. 64 The incidence of PVT in the warfarin group (15%) was 3-fold lower than that in the control group (43%). 64…”
Section: Role Of Transjugular Intrahepatic Portosystemic Shunt For Portal Vein Thrombosis Treatmentmentioning
confidence: 82%
“…64 The incidence of PVT in the warfarin group (15%) was 3-fold lower than that in the control group (43%). 64…”
Section: Role Of Transjugular Intrahepatic Portosystemic Shunt For Portal Vein Thrombosis Treatmentmentioning
confidence: 82%
“…The leukocytosis in our study could be the result of the endotoxin that reaches the portal system and is capable to activate coagulation process and lead to thrombus. (7) Endotoxemia has long been discovered in patients with hepatic disorders at higher levels than in healthy individuals which increase progressively with the hepatic disease, depending on the Child-Pugh stage. (8) Acute infections are associated with an increased transient risk in the development of venous thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…TIPS was successfully placed in all patients (technical success rate 100%). The median follow-up time was 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months. The mean age of the patients was 58 years (95% CI, 54.1-61.9 years), of which 31 (73.0%) were males.…”
Section: Baseline Characteristicsmentioning
confidence: 99%